Credit supply shocks and household leverage: Evidence from the US banking deregulation - Brown, Sarah; Gray, Daniel; Montagnoli, Alberto (Journal of Financial Stability, 2019)
We use a quasi-natural experimental framework provided by the staggered removals of interstate banking restrictions to identify the effect of a credit supply shock on household finances in the US. Banking deregulation is found to have increased the propensity to hold debt, the amount of debt held and the level of leverage. We also find that the deregulation had a more pronounced effect on non-white headed households. Moreover, we show how deregulation increased debt and leverage at the middle and the top of the debt and leverage distributions. The credit supply shock also had a relatively large effect on non-white headed households at the top 20% of the debt distribution.